A Novel Disorder of Osteoporosis, Osteonecrosis, and Metaphyseal Fracture. (28th April 2020) - Zmierczak, Hans‐Georg; Taylor, Guy; Cundy, Tim
ABSTRACT: We describe two unrelated women who in their fifth decade developed a severe disorder characterized by large joint osteonecrosis and multiple minimal trauma fractures in both the axial and appendicular skeleton, including unusual metaphyseal fractures of the proximal tibia. Bone density testing showed borderline osteoporosis of the spine and osteopenia of the femur. Therapy with bisphosphonates and teriparatide failed to prevent further fractures. To our knowledge, this disorder has not been described previously. Investigations to date, including a genetic screen, have not revealed its cause. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.